Health, Community, and Spirituality: Evaluation of a Multicultural Faith-Based Diabetes Prevention Program. (March 2014) - Gutierrez, Jaime; Devia, Carlos; Weiss, Linda; Chantarat, Tongtan; Ruddock, Charmaine; Linnell, Jill; Golub, Maxine; Godfrey, Loyce; Rosen, Rosa; Calman, Neil
Purpose: The purpose of this study was to evaluate Fine, Fit, and Fabulous (FFF), a faith-based diabetes prevention program for black and Latino congregants at churches in low-income New York City neighborhoods. FFF includes nutrition education and fitness activities while incorporating Bible-based teachings that encourage healthy lifestyles. Methods: FFF is a 12-week, bilingual program developed by the Bronx Health REACH coalition, a Centers for Disease Control and Prevention-funded Center of Excellence for the Elimination of Disparities. This program has been implemented in 15 Bronx and Harlem churches, engaging a primarily black and Latino overweight and obese urban population. Pre–post surveys, nutrition tests, and weight logs were collected to assess knowledge, attitudes, and behaviors regarding healthy eating and physical activity. Results: Participants (n = 183) reported statistically significant improvements in knowledge and healthy behaviors from baseline. Increased numbers of participants reported exercising in the past 30 days, eating fruit daily, being able to judge portion sizes, and reading food labels. Statistically significant numbers reported that they ate less fast food and were less likely to overeat at follow-up. The average weight loss across churches was 4.38 lbs or 2% of participants' initial body weight. Significant differences were observed when stratifying by race/ethnicity. Conclusion: Evaluation results show FFF's success at engaging overweight adults in behavior changes related to healthy eating and exercise. FFF demonstrates the potential of faith-based health interventions to address obesity and diabetes risk in high-need communities of color.